The Influence of Direction and Value of Plastic Prestrain on Steady-State Creep Rate Using the Combined Isotropic-Kinematic Hardening Rule - Waniewski, M. (Engineering Transactions, 1984)
The effect of changing in direction and value of room temperature plastic prestrain on steady-state creep rate is experimentally investigated by applying combined loadings of axial and shear forces to the pure copper thin-walled tubular specimens. The constitutive equation is verified by employing the two different approaches-the notation of creep plastic potential and the properties of tensor functions representation.